DIAGNOSTICS OF GASOLINE FUEL SYSTEMS WITH DIRECT INJECTION - Bulgakov, M.; Булгаков, М. П.; Булгаков, Н. П. (Харьковский национальный автомобильно-дорожный университет, 2017)
A method of diagnosing fuel systems with direct injection by means of producing a pressure oscillation in a hydraulic accumulator is presented. Having obtained a signal from pressure sensor it is possible to register a pressure drop at the moment of injection. If the system has a malfunction, then the pressure drop will be higher.
ДІАГНОСТУВАННЯ БЕНЗИНОВИХ ПАЛИВНИХ СИСТЕМ З БЕЗПОСЕРЕДНІМ УПОРСКУВАННЯМ
ДИАГНОСТИРОВАНИЕ БЕНЗИНОВЫХ ТОПЛИВНЫХ СИСТЕМ С НЕПОСРЕДСТВЕННЫМ ВПРЫСКОМ
Keywords: diagnostics; direct injection; signal; malfuctional; oscillation; pressure sensor; waveform; condition; hydraulic accumulator; діагностування; форсунка; тиск; коливання; датчик; диагностирование; форсунка; давление; колебание; датчик; 621.436